Biochar/iron (BC/Fe) composites for soil and groundwater remediation: Synthesis, applications, and mechanisms. (May 2020) - Lyu, Honghong; Tang, Jingchun; Cui, Mengke; Gao, Bin; Shen, Boxiong
Abstract: Biochar/iron (BC/Fe) composites, such as nano zero-valent iron (nZVI)/BC, iron sulfide/BC, and iron oxide/BC, have been developed and applied to deal with various contaminants owing to their excellent physicochemical properties. This work summarizes the progress in the preparation of BC/Fe composites, the properties and applications of BC/Fe, and the mechanism of the synergistic effect between Fe and BC in the composites. Various methods, including pyrolysis, hydrothermal carbonization, fractional precipitation, and ball milling, have been used to synthesize BC/Fe composites. In addition, the introduction of stabilizers, such as carboxymethyl cellulose (CMC), in the fractional precipitation process further prevents the agglomeration of Fe particles, which enhances the stability and fluidity of the resultant composites to facilitate the application of the composites in soil and water remediation. The application of BC/Fe composites in water and soil remediation is discussed in three aspects based on the interaction mechanisms, namely adsorption, reduction, and oxidation. Overall, the composites showed the synergistic effect of BC and Fe owing to the combination of the specific properties of Fe, such as reduction, catalysis, and magnetism, which can enhance the properties of BC with a larger surface area, abundant functional groups, and increased electron transfer efficiency. This review systemically summarizes the recent developments in BC/Fe composites to maximize the efficiency of BC/Fe application in soil and groundwater remediation. Key challenges and further research needs are also suggested. Graphical abstract: Image 100 Highlights: BC/Fe composites can be divided into three types based on their functions. Synthesis methods play an important role in the combination of BC and Fe. This review reveals the mechanism of the synergistic effect between Fe and BC. This review maximizes the efficiency of BC/Fe application.